ENHANCING HOUSEHOLD ECONOMIC EMPOWERMENT THROUGH ENTREPRENEURSHIP-ORIENTED HYDROPONIC TRAINING - Yuni Sri Rahayu; Yuliani Yuliani; Evie Ratnasari; Sari Kusuma Dewi; Novita Kartika Indah; Muhammad Zahrudin Afnan (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of urban areas has reduced productive land availability and increased food demands among urban communities. This condition also occurs in Menur Pumpungan Subdistrict, Surabaya, where limited green open spaces and underutilised household land reduce opportunities for household-based food production and productive economic activities. This community service program aimed to improve the knowledge and skills of residents, particularly PKK women groups, in household-scale hydroponic cultivation based on entrepreneurship. The program employed a participatory empowerment approach through preparation, implementation, evaluation, and reflection stages. Activities were conducted through lectures, demonstrations, hands-on practice, discussions, and mentoring related to simple hydroponic cultivation, the production of liquid organic fertilizer (LOF) from household organic waste, and entrepreneurship development. Program evaluation was carried out using observation, documentation, and participant response questionnaires with a Likert scale ranging from 1–5. The results showed that participants responded very positively to the program, with evaluation scores ranging from 4.0 to 4.9. The training also generated tangible impacts, including improved participant skills in implementing simple hydroponic systems at home, utilizing kitchen waste as liquid organic fertilizer, and increasing motivation to develop household-based businesses from hydroponic products. This program contributed not only to improving community knowledge and practical skills but also to strengthening women’s empowerment, household food security, and sustainable urban household economic resilience.